Basketball for boys and girls start right and play well - Gutman, Bill.; Brown, Ben, 1921- (Lakeville, Ct. : Grey Castle Press ; Freeport, N.Y. : M. Cavendish [distributor], 1990)
Describes the history and current teams, leagues, and championships of basketball and provides instruction on how to play the game.
Keywords: Basketball -- Juvenile literature; Basketball